2008
DOI: 10.1073/pnas.0712072105
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of tetrameric form of human lysyl-tRNA synthetase: Implications for multisynthetase complex formation

Abstract: In mammals, many aminoacyl-tRNA synthetases are bound together in a multisynthetase complex (MSC) as a reservoir of procytokines and regulation molecules for functions beyond aminoacylation. The ␣2 homodimeric lysyl-tRNA synthetase (LysRS) is tightly bound in the MSC and, under specific conditions, is secreted to trigger a proinflammatory response. Results by others suggest that ␣2 LysRS is tightly bound into the core of the MSC with homodimeric ␤2 p38, a scaffolding protein that itself is multifunctional. Not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
114
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 34 publications
(44 reference statements)
2
114
1
Order By: Relevance
“…These mutations were also effective in disrupting the dimeric interface of the protein, which was evident by DLS measurements and reduced aminoacylation activity. HIV-1 Gag and hLysRS are both capable of homodimer formation, as well as higher order oligomerization (14,29). However, previous work showed that homodimerization of these proteins is not important for their interaction, because a monomeric triple mutant variant still bound with an affinity within 2-fold of that of WT LysRS (21).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…These mutations were also effective in disrupting the dimeric interface of the protein, which was evident by DLS measurements and reduced aminoacylation activity. HIV-1 Gag and hLysRS are both capable of homodimer formation, as well as higher order oligomerization (14,29). However, previous work showed that homodimerization of these proteins is not important for their interaction, because a monomeric triple mutant variant still bound with an affinity within 2-fold of that of WT LysRS (21).…”
Section: Discussionmentioning
confidence: 93%
“…The published crystal structure (Protein Data Bank code 3bju) of LysRS (14) was first used to measure the largest end to end distance of the dimeric (ϳ10.7 nm) and monomeric (ϳ8.5 nm) proteins (Fig. 4B, inset).…”
Section: Lysrs Mutants Defective In Binding To Gag⌬p6mentioning
confidence: 99%
See 2 more Smart Citations
“…Blue residues are those that are affected by ACSL and WT TLE but not U9. The protein structure was generated using the hLysRS ACB domain coordinates (Guo et al 2008) and rendered using a protein surface.…”
Section: Summary Of Nmr Titration Resultsmentioning
confidence: 99%